Social Guidance Based on Local Wisdom: Building Social Resilience in the Midst of Cultural Change - Nina Siti Marlina (P3M STAI Kuningan, 2024)
Background: Communities worldwide are experiencing significant cultural change, challenging their social resilience and traditional support systems. Understanding how local wisdom can be systematically integrated into social guidance mechanisms represents a critical need for culturally grounded approaches to community resilience building.Objective: This study explores how local wisdom can be integrated into social guidance mechanisms to build social resilience in communities experiencing cultural change, identifying the dimensions, integration processes, success factors, and outcomes of such integration.Method: This qualitative study employed an interpretive phenomenological approach across multiple indigenous and traditional communities. Data were collected through in-depth interviews, focus group discussions, participant observation, and document analysis to capture the lived experiences and cultural practices of community members.Findings and Implications: The research identified five fundamental dimensions of local wisdom that contribute to social resilience: traditional ecological knowledge, social organization principles, cultural values, healing practices, and ceremonial traditions. Integration occurs through four primary mechanisms—formal institutionalization, educational programs, community-based initiatives, and digital documentation—with community-led grassroots approaches demonstrating the highest effectiveness. Success depends critically on political-legal recognition, strong traditional institutions, positive socio-cultural dynamics, and community sovereignty over cultural change processes. Local wisdom integration produces significant improvements in social cohesion, adaptive capacity, cultural identity, psychological well-being, and environmental management.Conclusion: Effective resilience building requires deep integration of local wisdom, critical engagement with traditional knowledge, and community control over cultural trajectories. This research contributes practical frameworks for culturally grounded development approaches that honor indigenous knowledge while supporting sustainable adaptation to contemporary challenges.